DAMPAK POLA ASUH OTORITER TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI (Studi Kasus Kelompok A di RA Attaqwa Padaringan, Kabupaten Ciamis) - Dede Aas (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
In a family, parents play a major role in influencing children's development, especially the social development of early childhood in adjusting well according to their age and maturity. Every parent has a different parenting style. The parenting style of the child will affect the social development and personality of the child. Parenting patterns in early childhood include providing physical, mental, emotional, moral, and social stimulation that will encourage optimal child development. This study will discuss issues related to the impact of authoritarian parenting on the socio-emotional development of early childhood in Group A RA Attaqwa Padaringan. The purpose of this article is to examine the impact of authoritarian parenting on the socio-emotional development of early childhood group A (aged 4-5 years). The method in this research uses qualitative methods with the type of case study research. Case studies are one of the research strategies that seek in-depth information about the research to be studied. Case study research is characterized by limitation to one part, description, and findings based on empirical evidence and facts. Results and Discussion This study states that authoritarian parenting has a positive but not significant effect on the development of emotional social intelligence in early childhood at RA Attaqwa Padaringan.